Manajemen Pajak Penghasilan pasal 21 - Nur Jannah; Sri Nirmala Sari; Imron Burhan (Income Journal: Accounting, Management and Economic Research, 2022)
This study aims to determine the application of tax management at PT Etam Wira Utama in conducting research on income tax article 21. This method is a qualitative descriptive method with data collection that applies the concept of profit and loss reporting at PT Etam Wira Utama. The results show that the application of tax management in saving income tax article 21 at PT Etam Wira Utama is in the form of supervision of tax transactions in the form of service delivery, in addition PT Etam Wira Utama manages transactions such as incentives in the form of other allowances that introduce at once and gradually . PT Etam Wira Utama's tax management in saving income tax article 21 is more concentrated on utilizing deductible costs, namely adding costs that can be used as deductions including salary costs and donation costs. The implementation of tax management has an impact on the amount of tax payable.